O programa e os métodos de treinamento profissional do curso de ferroviários da Companhia Sorocabana: São Paulo, década de 1930 - Zucchi, Bianca Barbagallo (2007)
The present study aims to reconstitute, based on the available documentation, the training program and methods of the Course for Railway Employees of Companhia Sorocabana, established in 1931 at the Professional School of Sorocaba. According to the historiography about professional teaching in Brazil, this course showed,in its results, the efficiency of the rationalization methods applied to workers education. This study will hopefully fill a knowledge gap about professional teaching in Brazil. Although some authors mention its importance among the initiatives to remodel the professional teaching that was taking place in the first half of the 20t h century, the Course for Railway Employees of Companhia Sorocabana had not been the object, up to the present moment, of a specific study on its training methods, its program and its students